Identification of BeO and BeOxDy in melted zones of the JET Be limiter tiles: Raman study using comparison with laboratory samples. (December 2018) - Kumar, M.; Makepeace, C.; Pardanaud, C.; Ferro, Y.; Hodille, E.; Martin, C.; Roubin, P.; Widdowson, A.; Dittmar, T.; Linsmeier, C.h.; Lungu, C.P.; Porosnicu, C.; et al.
Highlights: BeO and BeOx Dy vibrational modes have been detected on melted beryllium tile in JET. BeO was found as wurtzite whereas BeOx Dy is not detected as the known β-phase. D trapping occurs after melting through the formation of beryllium deuteroxides. Abstract: Beryllium oxide (BeO) and deuteroxide (BeOx Dy ) have been found on the melted zone of a beryllium tile extracted from the upper dump plate of JET-ILW (2011–2012 campaign). Results have been obtained using Raman microscopy, which is sensitive to both the chemical bond and crystal structure, with a micrometric lateral resolution. BeO is found with a wurtzite crystal structure. BeOx Dy is found as three different types which are not the β-phase but behaves as molecular species like Be(OD)2, O(Be-D)2 and DBeOD. The presence of a small amount of trapped D2 O is also suspected. Our results therefore strongly suggest that D trapping occurs after melting through the formation of deuteroxides. The temperature increase favors the formation of crystal BeO which favors deuterium trapping through OD bonding.